TINGKAT STRES DAN STATUS BEKERJA MENINGKATKAN KEJADIAN PREEKLAMSIA PADA IBU HAMIL - Zsalzsa Mella Aurellia; Elly Herwana (Jurnal Akta Trimedika, 2024)
Preeclampsia is a pregnancy complication with symptoms of hypertension and changes in organ function. Preeclampsia can occur in pregnancy starting from the 20th week and proteinuria is the most common functional disorder. Stress is a physical, emotional, mental and psychological response to environmental changes that require individuals to adapt. Stress trigger increased secretion of vasoactive hormones and other neurotransmitters, thereby increasing the risk of hypertension. This study aims to assess the relationship between stress and factors that influence preeclampsia in third trimester pregnant women. An analytical study with a cross-sectional design was conducted on third trimester pregnant women. Preeclampsia assessment is obtained based on secondary data on the patient's status. Stress levels were assessed using the DASS-21 questionnaire. The relationship between variables was analyzed using the Chi Square test with significance p<0.05. A total of 46 subjects participated in this study. The distribution of stress levels was found to be in the normal category, namely 23 (50%), mild stress levels were 16 (34.8%) and moderate stress levels were 7 (15.2%), there were no subjects with severe or very severe stress levels. The incidence of preeclampsia was found in 15 (32.6%) and 31 (67.4%) subjects did not  preeclampsia. There is a significant relationship between stress levels and preeclampsia (p=0.016; p<0.05). Educational level and working status were significantly related to preeclampsia (p=0.042; p=0.000; p<0.05)